Excessive Substitution of Fish Meal with Fermented Soybean Meal Induces Oxidative Stress by Impairing Glutathione Metabolism in Largemouth Bass (Micropterus salmoides) - Qiang Chen; Congcong Wang; Yulong Sun; Yan Chen; Songming Chen; Tao Han; Jiteng Wang (Antioxidants, 2023)
The application of fermented soybean meal (FSBM) is an effective strategy to alleviate the shortage of fish meal (FM) in aquaculture. However, an excessive substitution ratio often reduces fish growth and induces liver oxidative stress, while the mechanism remains poorly understood. Here, an 8-week feeding trial was conducted in largemouth bass (initial weight: 6.82 ± 0.09 g) to establish an oxidative stress model by replacing 50% of FM with FSBM (fermented by Bacillus subtilis). The results showed that FSBM substitution significantly reduced the growth performance of largemouth bass, including the weight gain rate and specific growth rate. Moreover, FSBM significantly reduced the contents of essential amino acids and total free amino acids in muscle, along with the mRNA expression of amino acids and small peptide transporters. Enzyme activity detection and liver sections showed that FSBM substitution caused liver oxidative stress, indicating the successful construction of an oxidative stress model. An integrated analysis of transcriptomic and metabolomic data revealed that FSBM substitution impaired glycine, serine and threonine metabolism, as well as glutathione metabolism. In addition, the ratio of reduced glutathione (GSH) to oxidized glutathione (GSSG) was decreased in the FSBM group, which may explain the mechanism of oxidative stress caused by FSBM substitution. Considering that glycine is an important component of glutathione synthesis, key genes involved in glycine metabolism (glya, gnmt and agxt) and dietary glycine supplementation should be valued to improve the availability of FSBM. This study reveals for the first time the importance of non-essential amino acids in improving the utilization of plant-based protein sources and provides original insight for the optimization of aquatic feeds.